2015
DOI: 10.1097/md.0000000000001526
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Surgical Outcome of 1057 Gastric GISTs According to 7th UICC/AJCC TNM System

Abstract: The aim of this study was to evaluate the treatment and prognosis of gastric gastrointestinal stromal tumors (GISTs) according to the 7th UICC/AJCC tumor-node-metastasis (TNM) system and the modified National Institutes of Health (NIH) risk classification. The study cohort consisted of 1057 patients with gastric GIST who underwent surgery between January 2000 and December 2007 from 13 institutions in Korea and 2 in Japan. Clinicopathologic characteristics, surgical outcomes, recurrence, and 5-year recurrence-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 15 publications
12
22
0
2
Order By: Relevance
“…The stomach is the most commonly affected GI site in patients with a localized GIST, and is associated with the most favourable prognosis, with a 5-year survival rate of 84⋅5 per cent reported in the present study. This is comparable with survival data from other studies 33 , including a large cohort from Korea and Japan 34 . There may be a bias in these survival rates when compared to other GI locations, because gastric GISTs are generally discovered at an earlier disease stage.…”
Section: Discussionsupporting
confidence: 89%
“…The stomach is the most commonly affected GI site in patients with a localized GIST, and is associated with the most favourable prognosis, with a 5-year survival rate of 84⋅5 per cent reported in the present study. This is comparable with survival data from other studies 33 , including a large cohort from Korea and Japan 34 . There may be a bias in these survival rates when compared to other GI locations, because gastric GISTs are generally discovered at an earlier disease stage.…”
Section: Discussionsupporting
confidence: 89%
“…Most (61%) of the cases were classified under 'high risk'. As reported from other studies [15,16] liver was the most common site of metastasis in our patients. However, pulmonary metastases, which have been described as 'rare' in GISTs [17], and a sign of advanced disease [4], was the second most common site of metastases in our study.…”
supporting
confidence: 86%
“…However, despite the similarities in IHC and genetic testing between eGISTs and GISTs, the prognoses of eGISTs are less favorable compared to GISTs as the former tends to have higher proliferative mitotic indices (GISTs vs eGISTs, median range, 4–8/50 HPF 36 38 vs 10–15/50 HPF 12 , 39 , 40 ), larger tumor size (GISTs vs eGISTs, median range, 4–7 cm 38 , 41 , 42 vs 7.5–15 cm 12 , 14 , 39 , 40 , 43 ) and greater risk to recurrence or distant metastasis. 14 , 44 Similarly, our findings showed that the median tumor size (13 cm, range, 0.4–29 cm) and mitotic value (13 HPF, range, 0–50 HPF) were in accordance with that of reported literature.…”
Section: Discussionmentioning
confidence: 99%